2015
DOI: 10.1021/acs.jafc.5b04814
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grape Seed Proanthocyanidin–Gelatin Colloidal Complexes on Stability and in Vitro Digestion of Fish Oil Emulsions

Abstract: The colloidal complexes composed of grape seed proanthocyanidin (GSP) and gelatin (GLT), as natural antioxidants to improve stability and inhibit lipid oxidation in menhaden fish oil emulsions, were evaluated. The interactions between GSP and GLT, and the chemical structures of GSP/GLT self-assembled colloidal complexes, were characterized by isothermal titration calorimetry (ITC), circular dichroism (CD), and Fourier transform infrared spectroscopic (FTIR) studies. Fish oil was emulsified with GLT to obtain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 44 publications
(75 reference statements)
0
21
0
1
Order By: Relevance
“…Furthermore, Liu et al ( 32 ) calculated the emulsifying activity index (EAI) and emulsion stability index (ESI) parameters of the unmodified LF and LF–polyphenol complexes, and the results showed that the ESI of LF–EGCG was improved and the emulsion stability was higher than that of LF ( 32 ). In addition, gelatin–anthocyanin complexes can change the functional properties of hydrophilic gelatin proteins and thus improves the stability of emulsions ( 49 ).…”
Section: Types Of Protein–polyphenol Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Liu et al ( 32 ) calculated the emulsifying activity index (EAI) and emulsion stability index (ESI) parameters of the unmodified LF and LF–polyphenol complexes, and the results showed that the ESI of LF–EGCG was improved and the emulsion stability was higher than that of LF ( 32 ). In addition, gelatin–anthocyanin complexes can change the functional properties of hydrophilic gelatin proteins and thus improves the stability of emulsions ( 49 ).…”
Section: Types Of Protein–polyphenol Complexesmentioning
confidence: 99%
“…Moreover, studies showed that the release rate of free fatty acids in fish oil emulsions stabilized by gliadin-grape seed proanthocyanidins (GSP) complexes was lower than that of normal emulsions. It can be concluded that the digestion time of normal emulsion was 20 min, and that of complexes stabilized emulsion was longer, with free fatty acid release rates of 92.5 and 63.3%, respectively ( 49 ). The results showed that the digestibility of emulsion stabilized with gliadin–GSP was lower than that of free gliadin.…”
Section: Effect Of Protein–polyphenol Complexes On Stability Of Emulsionsmentioning
confidence: 99%
“…The PAs supernatant was collected for follow‐up experiment by centrifugation (6000 × g , 15 min), with the final concentration of 2% (w/v) for PAs solution. ZPAPs were acquired by self‐assembly method based on previously study with slight modification (Su et al ., 2015). Our preliminary experiment results showed that the emulsion stabilised by the zein‐PAs complex (mass ratio = 2:1) had stronger stability than those by other ratios.…”
Section: Methodsmentioning
confidence: 99%
“…Grape seed proanthocyanidin (PAs), an oligomer and polymer of flavan‐3‐alcohol, has multiple biological activities such as antioxidation, antitumor and antivirus (Unusan, 2020). However, the low solubility in oil limits the bioavailability of PAs in food oil system (Su et al ., 2015) It has been reported that proanthocyanidins readily interact with proline‐rich proteins through hydrogen bonds (Ma et al ., 2021). Girard et al ., (2018) investigated the mechanisms of proanthocyanidins and wheat gluten proteins and found that they were non‐covalent binding.…”
Section: Introductionmentioning
confidence: 99%
“…The emulsions stabilized by WPMP and WPMP-XG complexes were stored at 30 °C for 17 d. Every 24 h, 2 g samples of each emulsion were placed in a flask and dissolved with 6 mL of a mixture of trichloromethane/methanol (7:3, v:v) [ 15 ]. After vortexing three times, the mixture was centrifuged at 10,000× g for 5 min.…”
Section: Methodsmentioning
confidence: 99%